The critique of Gikuyu religion and culture in S.N. Ngubiah's A Curse from God - F. Hale (Acta Theologica)
The relationship between missionary Christianity and traditional African cultures was a prominent theme in post-colonial literature during and for many years after the era of decolonisation. In contrast to the nostalgic defensiveness of many Kenyan and other post-colonial African writers, perhaps most notably Ngugi wa Thiong’o, the Gikuyu novelist S.N. Ngubiah found not salvation but a burden in certain aspects of his precolonialist indigenous culture. In his novel A curse from God (1970) Ngubiah challenges obliquely but unmistakably the long-accepted position of his fellow Gikuyu (and first national leader of independent Kenya) Jomo Kenyatta, particularly as argued in Facing Mount Kenya, that a return to tribal folkways was a precondition to economic and social upliftment. This clash between a traditionalist and a modernist exemplifies the larger predicament facing African societies as they undergo rapid religio-cultural transformation.